2013
DOI: 10.1080/01652176.2013.775833
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid utilization by the hindlimb of warmblood horses at rest and following low intensity exercise

Abstract: Further investigation is necessary into the specific role of leucine supplementation to preserve or restore body protein in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
0
1
Order By: Relevance
“…An increase in protein synthesis was observed at 204 μM as well as at 408 μM leucine but not at 102 μM leucine (P < 0.02; Figure 2). Average plasma leucine concentrations in the horse range between 80 and 160 μM (Westermann et al, 2011;Peters et al, 2013;Mastellar et al, 2016) just below the concentration at which statistical differences were observed in this study. No effect was observed between 25 and 102 μM leucine, suggesting that in these experiments those concentrations did not reach the threshold needed to detect an increase in 3 H-Phe incorporation into equine satellite cell proteins.…”
Section: Protein Synthesis Assaycontrasting
confidence: 60%
“…An increase in protein synthesis was observed at 204 μM as well as at 408 μM leucine but not at 102 μM leucine (P < 0.02; Figure 2). Average plasma leucine concentrations in the horse range between 80 and 160 μM (Westermann et al, 2011;Peters et al, 2013;Mastellar et al, 2016) just below the concentration at which statistical differences were observed in this study. No effect was observed between 25 and 102 μM leucine, suggesting that in these experiments those concentrations did not reach the threshold needed to detect an increase in 3 H-Phe incorporation into equine satellite cell proteins.…”
Section: Protein Synthesis Assaycontrasting
confidence: 60%